Simulating thermochromic and heat mirror glazing systems in hot and cold climates - Kokogiannakis, Georgios; Darkwa, Jo; Aloisio, Cristina (2014)
This paper investigates the potential energy requirements for heating and cooling when using a thermochromic glazing system on a highly glazed tall office building and comparisons are made with the respective performance of two heat mirror units and a clear triple glazed window. The assessment is done with the ESP-r whole building integrated simulation program in order to account for the dynamic optical properties of thermochromic glass in integrated simulations. The glazing systems are assessed for hot, cold and significantly varying between hot and cold climates. Annual heating and cooling energy requirements were quantified and short-period simulations were also run to assess the effect of the glazing systems on indoor temperatures. It was found that thermochromic glazing could significantly reduce cooling loads in hot climates and where cooling could be a significant building energy load (by approximately 30% in comparison with the other glazing systems). On the other hand, thermochromic glass could have a negative impact in cold climates where the use of heat mirror glazing systems could offer the highest energy savings even when compared with the triple glazed window. In seasonally varying climates and for highly glazed office buildings in which simultaneous high internal and solar heat gains are likely to occur, the use of thermochromic glass is an appropriate technique for saving energy and improving thermal comfort.